After the Ice Age: The Impact of Post-Glacial Dispersal on the Phylogeography of a Small Mammal, Muscardinus avellanarius - Combe, Fraser J.; Ellis, Jonathan S.; Lloyd, Kirsty L.; Cain, Bradley; Wheater, C. Philip; Harris, W. Edwin (Frontiers in Ecology and Evolution, 2016)
We used genetic tools to assess phylogeographic structure of the common dormouse (Muscardinus avellenarius) since the end of the last glacial maximum, to identify post-glacial dispersal routes and to describe population units for conservation. Comparative analysis of mitochondrial genes (Cytochrome b 704 bp, D-loop, 506 bp) and one nuclear gene (Beta-Fibrinogen, 550 bp) was conducted to reconstruct the recent demographic history within and between UK and Continental European populations. Our analysis indicated phylogeographic variation similar in magnitude to that found in other regions of Continental Europe and suggests a recent population expansion. We present evidence which supports a single post-glacial colonization into the UK. Dispersal time calculations, calibrated with geophysical events, are coincident with the start of the Holocene period, 7.5-11 kya, a time when geological evidence suggests temperatures were stable, woodland habitat was prevalent and a land bridge was present to allow the dispersal of small mammals into the UK. We discuss our findings in the context of the extant geographical genetic structure described here and in relation to conservation management of this threatened species.